Pengaruh Densitas Lost foam Dan Temperatur Tuang Terhadap Porositas Dan Densitas Coran Kuningan - Purnayasa, I Kadek Suka; Sugita, I Ketut Gede; Priambadi, I.G.N. (Teknik Desain Mekanika, 2022)
Abstract The use of metal in products made of brass has a complicated shape, for example, that used in interior rooms and religious ceremony facilities often has the stigma of castings in the final output as a result of being out of sync with the designs made. Evaporative casting (lost foam) is one of the methods used to get a more aphoristic output because it is easy to adjust according to desire. The density of Polystyrene foam used was 0.012, 0.014, 0.016, 0.018 gr/cm3 using various pouring temperatures of 900, 950 & 1000 oC. Coating using alumina silica, gypsum & white cement is used in the mold pattern The highest density value of brass castings is produced in specimens using a density of 0.012 gr/cm3 Polystyrene foam at a temperature of 900oC as much as 8,669 gr/cm3 using a porosity of 0.69%, while the density value of castings The lowest brass was produced in the specimen using 0.018 gr/cm3 Polystyrene foam at a temperature of 1000 oC as much as 8,178 gr/cm3 using 6.32% porosity. The SEM test indicated an increase in porosity as the Polystyrene foam density and pouring temperature increased. . Keywords: lost foam Casting, Brass, Polystyrene foam